AB0959 The Role of Ultrasonography in the Early Diagnosis of Arthropathy in A not Target Joint of Haemophiliacs. (10th June 2014) - Melchiorre, D.; Linari, S.; Morfini, M.; Bandinelli, F.; Matucci-Cerinic, M.
Abstract : Background: The hip is not a target joint in haemophilic arthropathy (HA). Patients (pts) with Haemophilia have hip pain without obvious signs of joint involvement. They have, very often, haematoma or bursitis. Objectives: To investigate the role of ultrasonography (US) to detect bleeding and joint damage HA of the hip. Methods: In 30 pts, with Haemophilia and monolateral hip pain, the iliopsoas and its bursa, the greater trochanteric bursae, and the joint were studied by US. The 30 joints were evaluated and scored (score ranging from 0 to 21) for effusion, bone remodelling, cartilage damage, synovial hypertrophy, haemosiderin, osteophytes, haemarthrosis, erosion and fibrotic septa. The clinical evaluation [World Federation Haemophiliac orthopaedic score (WFHO)] was done in all pts. Power Doppler US (PDUS) was performed in all patients. Results: US showed effusion in 20 joints, bone remodelling in 18, cartilage damage in 10, synovial hypertrophy in 12, haemosiderin in 4, osteophytes in 7, haemarthrosis in 10 with PDUS activity, erosion in 0 and fibrotic septa in 0. In haemophiliacs 15 out of 30 joints showed US score ≤5, and 15 US score >5 (1, 2). In 8 pts was present haematoma of iliopsoas, in two pts great trocanteric bursitis. Conclusions: US detected bone and cartilage alterations and synovitis in the hip. Indeed PDUS identified the bleeding in the joints and was able to show different entity of haemarthrosis. US may be useful to evaluate joint modifications in HA in no target joint, too. References: Melchiorre D, et al. Haemophilia 2011, 17:112-7 Querol F, et al. Haemophilia 2012, 18:e215-e226 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4391